Persepsi Masyarakat terhadap Dampak Dinamika Politik dalam Kebijakan BPJS Kesehatan di Puskesmas Tuntungan - Nasution, Irfan Sazali; Rara Aulia Alzazira; Dhea Syapira; Cindi Aulia Ali; Efrida Efrida; Nayla Raihani Malau; M. Daffa Almuzaki (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
This study aims to investigate the perceptions of the community in Puskesmas Tuntungan, Jl. Kutalimbaru, Desa Tuntungan I, Kecamatan Pancur Batu, Kabupaten Deli Serdang, Sumatera Utara, regarding the impact of political dynamics on BPJS Health policy in Puskesmas Tuntungan. Using a quantitative approach with 100 respondents, the results show that the majority of respondents are aware of the frequent changes in BPJS policy. This study concludes that the community has diverse and critical perceptions of the dynamics of BPJS Health policy and its relation to political conditions.